IMPLICATION OF SOCIAL ISOLATION ON MENTAL HEALTH DURING THE COVID-19 PANDEMIC: A LOOK AT ITS RELIGIOUS AND SPIRITUAL COPING - Gohar, Amna [UNESP]; Carvalho, Alonso Bezerra de [UNESP]; Brandao, Carlos da Fonseca [UNESP] (Unesp-faculdade Ciencias & Letras, 2021)
China was the center of Covid-19 which rapidly spread out all over the world. The rapid outbreak of Covid-19 in Asian countries has severely affected psychological and social life of people. Which also has a great influence on religion and faith. Spiritual and religious copping is an effective approach for mental relaxation and belief on the creator specifically during the Covid-19 outbreak. The main purpose of this study is observing the situation of Asian countries existing literature on human psychology and social life further it also explores religious and spiritual coping during Covid-19. Different studies were retrieved from online sources. In which the published articles were classified according to three themes such as human psychology, religious and spiritual coping and social life during Covid-19. It is evident from the literature that covid-19 has a great influence on human psychology. Majority people suffered from anxiety and depression in these tough days of life. Also, most of the people suffered from fear, depression, stress, loneliness during lockdown which effects their social life. The positive point was found that religion and spirituality helping people to reduce their stress and create positivity in their life. Spirituality helps out people in mental relaxation at times of crisis and epidemic situations while religious copings and strong believe on creator reduce anxiety and depression.
Keywords: Religiosity; Spirituality; Human psychology; Social life; Covid-19